An online educational portal for supporting open access to teaching and learning of people with disabilities - Zervas, P.; Kardaras, V.; Sampson, Demetrios (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 IEEE. Accessibility has emerged as a core consideration of systems' design in the Technology enhanced Learning (TeL) field. This ensures that technology does not introduce barriers to the inclusion of people with disabilities but rather it offers equal opportunities to education and training. Within this context, several initiatives have emerged, which aim to promote an inclusive learning culture and support teachers in designing, sharing and delivering accessible educational resources in the form of Learning Objects (LOs). To this end, in this paper we present an online educational portal, namely the Inclusive Learning Portal that aims to advance existing solutions and support open access to teaching and learning of people with disabilities, namely motor disabled, visual impaired and deaf people.